Improving Sales Performance Using SWOT Analysis in Surabaya Digital Marketing Services - Elvina Shafa Nabilah; Tri Wahjoedi (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
Digital marketing is an advertising activity that uses quality online media on the internet network. By using the company's theme products, your atmosphere can be edited through the Canva application, Adobe Photoshop to make video content as attractive as possible. With an application that makes it easy for business people to sell products and promote their products directly on a regular basis using existing media. All business leaders will compete with those who really strengthen technological progress, so your business can survive in this digitalization era successfully and purposefully to achieve company goals by taking the right steps so that consumers are not disappointed with producer performance services. Behind the popularity of digital technology, it is making it easier for people to sell various services and business products. In compiling this internship report, a qualitative method uses information gathering by the author by direct observation at